Effectiveness of Ai Chi as Aquatic Intervention for Balance Impairments in Community-dwelling Older Adults in India: A Randomised Controlled Study - Purnima Singh; Pratap Chandra Sarma (Journal of Clinical and Diagnostic Research)
Introduction: Balance impairment is a significant concern for older adults in India and worldwide, as it increases the risk of falls and affects quality of life. Aquatic therapy, particularly Ai Chi, which is not a widely popular intervention in India, offers a low-impact approach to improving balance. Aim: To investigate the effectiveness of Ai Chi in improving balance among community-dwelling older adults compared to conventional aquatic therapy. Materials and Methods: This randomised controlled trial investigated the effectiveness of Ai Chi compared to Conventional aquatic therapy (Control group) in improving balance among community-dwelling older adults. Thirty participants aged 60 and above with balance impairments were randomly assigned to either the Ai Chi or control group. Both groups received 40-minute aquatic therapy sessions three times a week for eight weeks. Balance was assessed using the Berg Balance Scale (BBS), Timed Up and Go Test (TUGT), and Dynamic Gait Index (DGI) before (P1), after four weeks (P2), and after eight weeks of intervention (P3). An Independent t-test was used for between-group analyses, and a Dependent t-test was used for within-group analysis. A Bonferroni test was applied to analyse differences between groups. Results: The participants had a mean age of 72 years, ranging from 65 to 80 years. The mean baseline scores for the BBS, TUGT, and DGI were 39.06, 13.33, and 14.13, respectively. After four weeks of intervention, the mean scores improved to 42.03, 11.73, and 15.69 for the BBS, TUGT, and DGI, respectively. Following the eighth week of intervention, the mean scores further improved to 46.23, 10.66, and 16.23 for the BBS, TUGT, and DGI, respectively. There were significant differences between the pretest and post-test 1 (MD=3.80, p-value=0.005), post-test 1 and post-test 2 (MD=4.8, p-value <0.001), and between the pretest and post-test 2 (MD=8.608, p-value <0.001). These analyses indicated that measures of static and dynamic balance improved consistently in both the groups. A post-hoc analysis of BBS scores showed both short-term and long-term improvements in the Ai Chi group compared to the control group. Conclusion: The study concluded that Ai Chi is an effective and enjoyable intervention for enhancing balance and potentially reducing the risk of falls and improving overall quality of life in older adults.